2020
DOI: 10.1007/s40544-020-0363-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of friction on the contact stress of a coated polymer gear

Abstract: Polymer gears are used extensively in various applications. However, durability issues have been emerging because of friction at gear tooth contact areas. To extend the lifetime of polymer gears, a low-frictional coating has been considered as a possible strategy. In this study, a finite element simulation method was performed to investigate the contact stress between a pair of coated polymer gears. The simulation included various friction coefficients (COFs) for studying the effects of friction during the ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…7, H and I) (58). According to previous studies (59,60), an additional bending effect at the edges of the contact zone coating can be caused by the groove geometry and the pile-ups. This bending can, in turn, result in generation of compressive and tensile stresses in addition to the stresses caused by the contact.…”
Section: Fe Simulationmentioning
confidence: 86%
“…7, H and I) (58). According to previous studies (59,60), an additional bending effect at the edges of the contact zone coating can be caused by the groove geometry and the pile-ups. This bending can, in turn, result in generation of compressive and tensile stresses in addition to the stresses caused by the contact.…”
Section: Fe Simulationmentioning
confidence: 86%
“…The experimental results indicated that the PTFE-coating provided the greatest reduction of friction and wear for the analysed polymer gears. Furthermore, Bae et al [ 31 ] proposed an FEM-model to investigate the contact stress response of a coated polymer gear with the frictional effect during gear operation. Their numerical results have shown that a coating of 2 μm thickness had a negligible effect on the contact stress during the mesh cycle, because the thickness was insufficient to affect the bulk deformation behaviour of the polymer gears.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [21] studied the calculation method of friction coefficient and meshing efficiency of plastic wire gear pair under dry friction condition, the dynamic characteristics of the system under dry friction condition are obtained. Bae et al [22] adopts finite element simulation method to the contact stress between coated polymer gears considering different friction coefficients. Keller et al [23] established a thermal elastohydrodynamic model for the single tooth gear.…”
Section: Introductionmentioning
confidence: 99%